Co-production of polyhydroxyalkanoates and levan by Halomonas smyrnensis AAD6T (Research, Society and Development, 2022)
The simultaneous production of microbial polymers levan and poly[3-hydroxybutyrate] (PHB), a type of polyhydroxyalkanoates, was investigated in this work. The study involved the fermentation of sucrose and molasses by H. smyrnensis AAD6T (BAE2 strain) to produce PHB (intracellular) and levan (extracellular). Both polymers were isolated and characterized by FTIR. Levan was also characterized by thin-layer chromatography (TLC) and viscosimetric analysis. The amount of biomass was 25 g until the end of fermentation. The PHB rate was 0.015 g in both media and the average PHB productivity was 6.0 x 10-4 g PHB/g biomass. The highest rate of levan was 9 g/L in the range of 72–80 h, in the molasses-based medium. The FTIR spectra showed specific signals for each of the polymers, such as the peak at 1700 for the carbonyl group of esters for the PHB and signals at 900 and 800, which are typical signals for levan fructose rings. Furthermore, acid hydrolysis of levan revealed that it was formed only by fructose, as confirmed by TLC With this study, H. smyrnensis AAD6T BAE2 co-produced PHB and levan using a low-cost carbon source, showing great potential in reducing biopolymer manufacturing costs.